2021
DOI: 10.1080/02678373.2021.1976882
|View full text |Cite
|
Sign up to set email alerts
|

Daily effects of face-to-face and cyber incivility via sadness, anger and fear

Abstract: including the URL of the record and the reason for the withdrawal request.Daily Effects of Incivility via Discrete Emotions 1 Daily Effects of Face-to-face and Cyber Incivility via Sadness, Anger and FearMany workers are subjected to incidents of rudeness and ignorance at work. Emerging evidence suggests that exposure to such incivility has an immediate impact on people's daily well-being and commitment. In this article we contribute to this nascent area of enquiry by investigating the role of discrete emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…The workforce exhibits normative reactions and is unlikely to stay at their current employment if they are subjected to workplace incivility (Britt and Jex, 2015). The same has been proven in past studies as well (Cortina et al, 2001) in terms of turnover intention (Alola et al, 2021;Niven et al, 2021;Singh and Vashisht, 2021). The victims of workplace incivility may become disinterested in their employment and seek job replacement (Wu and Chi, 2020).…”
Section: Workplace Incivility and Job Search Behavioursupporting
confidence: 63%
See 2 more Smart Citations
“…The workforce exhibits normative reactions and is unlikely to stay at their current employment if they are subjected to workplace incivility (Britt and Jex, 2015). The same has been proven in past studies as well (Cortina et al, 2001) in terms of turnover intention (Alola et al, 2021;Niven et al, 2021;Singh and Vashisht, 2021). The victims of workplace incivility may become disinterested in their employment and seek job replacement (Wu and Chi, 2020).…”
Section: Workplace Incivility and Job Search Behavioursupporting
confidence: 63%
“…The victims may start ignoring the instigator, deliberately lower their work efforts, be silent on organizational matters, gradually develop turnover intentions and exhibit job search behaviour. Several prior studies have examined the impact of workplace incivility on a range of damaging consequences, including turnover intention (Alola et al , 2021; Niven et al , 2021), organizational silence (Tutar et al , 2021), counterproductive work behaviour (Butt and Yazdani, 2021), deviant silence (Khan et al , 2021), psychological distress (Abubakar et al , 2018), knowledge hiding (Anand et al , 2022), job search behaviour (Hassan et al , 2022), emotional exhaustion (Moon and Morais, 2022) and many others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that previous studies have explored the relationship between cyber incivility and negative emotions, this research pays specific attention to emotional exhaustion. Previous studies indicated a positive correlation between general cyber incivility and emotional exhaustion (Niven et al, 2022). As the active and passive dimensions may have different effects, we would like to analyze whether this difference exists on emotional exhaustion.…”
Section: Introductionmentioning
confidence: 98%
“…Boudrias et al (2021), upon reviewing relevant literature, found that the effect of toxic behaviors such as bullying broadly falls into three categories; health impairments, occupational outcomes and personal and family domain outcomes. The psychological impact of toxicity on employees persists for a long time owing to the escalation of sadness, anger and fear, which culminates in constant emotional fatigue and a drain on mindfulness states (Niven et al, 2021;Said and Tanova, 2021). In short, in light of the pervasive effect of workplace toxicity, a significant number of companies are concentrating more on tackling the problem due to the following reasons.…”
Section: Introductionmentioning
confidence: 99%